Narratives in Psychiatry. - Shergill, Sukhwinder Singh (Jessica Kingsley Publishers, 2002)
'This book serves to remind us that in psychiatry the diagnosis, course, treatment and outcome of disorders rest heavily on the extraordinarily complex and sensitive relationship between doctor and patient ... with its emphasis on narrative, meaning, the relationship between subjective experience and objective reality, [it] reasserts the primary truth of medicine, namely that establishing the true picture of health and disease requires the active participation of the patient at every stage ... how are we to avoid losing sight of the person in the midst of bleeping machines and flickering computer.